2016
DOI: 10.2174/1381612822666151214125950
|View full text |Cite
|
Sign up to set email alerts
|

The Kynurenine Pathway in the Acute and Chronic Phases of Cerebral Ischemia

Abstract: Kynurenines are a wide range of catabolites which derive from tryptophan through the “Kynurenine Pathway” (KP). In addition to its peripheral role, increasing evidence shows a role of the KP in the central nervous system (CNS), mediating both physiological and pathological functions. Indeed, an imbalance in this route has been associated with several neurodegenerative disorders such as Alzheimer’s and Huntington’s diseases. Altered KP catabolism has also been described during both acute and chronic phases of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 203 publications
2
16
1
Order By: Relevance
“…However, these striking similarities were observed within the first hour in humans and first half hour in rats after resuscitation, indicating that unlike previous studies, alterations in the tryptophan and kynurenine pathway metabolites occur almost immediately postresuscitation. A higher kynurenine to tryptophan ratio observed in both preclinical and clinical studies of brain injury [48][49][50][51] and cardiovascular disease 52 indicated worse clinical outcomes implicating oxidative and inflammatory stress. Controversially, ischemic damage induced by CA may increase kynurenic acid, which may serve a protective role, as kynurenic acid has neuroprotective effects, while 3-hydroxyanthranilic acid and downstream quinolinic acid have a proclivity for neurotoxicity 50,53 .…”
Section: Discussionmentioning
confidence: 99%
“…However, these striking similarities were observed within the first hour in humans and first half hour in rats after resuscitation, indicating that unlike previous studies, alterations in the tryptophan and kynurenine pathway metabolites occur almost immediately postresuscitation. A higher kynurenine to tryptophan ratio observed in both preclinical and clinical studies of brain injury [48][49][50][51] and cardiovascular disease 52 indicated worse clinical outcomes implicating oxidative and inflammatory stress. Controversially, ischemic damage induced by CA may increase kynurenic acid, which may serve a protective role, as kynurenic acid has neuroprotective effects, while 3-hydroxyanthranilic acid and downstream quinolinic acid have a proclivity for neurotoxicity 50,53 .…”
Section: Discussionmentioning
confidence: 99%
“…Neurologic dysfunction is common in patients with encephalitis and bacterial meningitis, and dysregulation of the KP has been shown in syndromes and disorders with certain overlap in symptoms [ 21 , 30 , 32 , 56 , 57 ]. Herein, we compared these metabolites in patients with a stringent definition of etiology; encephalitis, confirmed viral meningitis, and bacterial meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…In the acute ischemic phase, the tissue is affected by a sequence of molecular and cellular events due to a decrease in the CBF. This sequence of events is called the ischemic pathway, which begins with energy depletion and glutamate excitotoxicity, and ends in cell death (Lai et al, 2014;Cuartero et al, 2016; Figure 1). According to the changes in membrane potential, the most vulnerable cells to 30-min OGD are neurons, followed by astrocytes, while NG2 glia showed no significant pathological alterations (Du et al, 2018).…”
Section: Phases Of Ischemiamentioning
confidence: 99%